Isolation, Optimization and Characterization of Rhodotorula alborubescens for Dietary Pigment β-Carotene Production - Anshi; Hardeep Kaur; Lalit Goswami; Shikha Kapil; Vipasha Sharma (Applied Microbiology, 2025)
In this study, pigment-producing yeast (Rhodotorula alborubescens) was isolated from the soil sample, demonstrating the potential for carotenoid biosynthesis. Physiological, morphological, biochemical, and molecular characterization confirmed the identity of the isolate. Optimization of the physical parameters for carotenoid production was achieved through batch shake flask experiments. The optimal conditions were determined to be 84 h of incubation at pH 6.0 and 28 °C under white light irradiation, utilizing the Yeast Peptone Dextrose (YPD) medium composed of 10 g/L yeast extract, 5 g/L of peptone, and 5 g/L dextrose, resulting in maximum carotenoid content. Further, the presence of β-carotene was confirmed using High-Performance Liquid Chromatography and Fourier Transform Infrared Spectroscopy. These findings highlight the potential of the isolated soil yeast (R. alborubescens) as a potential source of carotenoids, offering natural alternatives for various industrial applications.